Correction: Healthy lifestyle behaviors are major predictors of mental wellbeing during COVID-19 pandemic confinement: A study on adult Arabs in higher educational institutions - Kilani, Hashem A.; Bataineh, Mo’ath F.; Al-Nawayseh, Ali; Atiyat, Khaled; Obeid, Omar; Abu-Hilal, Maher M.; Mansi, Taiysir; Al-Kilani, Maher; Al-Kitani, Mahfoodha; El-Saleh, Majed; Jaber, Ruba M.; Sweidan, Ahmad; et al. (PLOS ONE, 2025)
null